Infant Iron Stores at Three Months of Age Are Associated With Maternal Hepcidin and Serum Ferritin Concentrations During the Second Trimester. (14th June 2022) - Evanchuk, Jenna; Hanas, Natalie; Goruk, Susan; Bell, Rhonda; Kozyrskyj, Anita; O'Brien, Kimberly; Field, Catherine
Abstract: Objectives: To determine if relationships exist between maternal concentrations of hepcidin and serum ferritin (SF) throughout pregnancy and infant SF concentrations at 3 months of age. Methods: Pregnant women from Edmonton and Calgary, Alberta, Canada were recruited into the Alberta Pregnancy Outcomes and Nutrition (APrON) cohort study from 2009–2012. Blood samples were collected from 358 women at each trimester of pregnancy and their infants at 3 months of age. Maternal hepcidin concentrations were assessed using enzyme linked immunosorbent assays. Maternal and infant SF concentrations were measured by chemiluminescent microparticle immunoassays. General linear models and multiple regression models, adjusting for maternal age, ethnicity, pre-pregnancy body-mass-index, and inflammation via direct acyclic graphs, were performed by SAS−9.4. Results: In the maternal cohort, 63.4% had suboptimal iron stores (SF < 15 ng/mL) during late gestation. Infant SF concentrations were ordered into quartiles arranged by maternal SF and hepcidin concentrations (Q1 being the highest). During the second trimester, women with hepcidin concentrations in Q3 (4.8–9.9 ng/mL) had infants with significantly higher concentrations of SF at 3 months [β = 39.6 ng/mL (11.6, 67.6); p = 0.013], compared to those in Q1, Q2, and Q4. Infant SF concentrations were significantly higher when second trimester maternal SF concentrations were in Q2 (31.5–46.5 ng/mL) [β = 33.1 ng/mL (5.6, 60.5); p = 0.018] and Q3 (18.0–31.4 ng/mL) [β = 30.8 ng/mL (3.5, 58.2); p = 0.027] compared to Q1 and Q4. There were no relationships between maternal SF and hepcidin concentrations during the first or third trimesters and infant SF concentrations. A positive relationship was found between maternal hepcidin and SF concentrations during mid-gestation (P < 0.0001), which may partly explain why higher infant SF concentrations were similarly associated with moderate maternal concentrations of both iron biomarkers. Conclusions: Second trimester maternal concentrations of SF (18.0–46.5 ng/mL) and hepcidin (4.8–9.9 ng/mL) were associated with higher SF concentrations in 3-month-old infants. Future studies are needed to explore the complex relationships between maternal iron status and infant iron status during the first year of life. Funding Sources: APrON study by Alberta Innovates, CIHR; J. Evanchuk by CIHR, WCHRI.